The relationship between student’s perceptions of their school environment and academic achievement - Edgerton, Edward; McKechnie, Jim (Frontiers in Psychology, 2023)
Research within an educational context has demonstrated the importance of variables such as socioeconomic status, gender and school attendance as predictors of academic achievement, however research investigating the impact of the physical learning environment on academic achievement is more limited and what research has been conducted often focuses on objective characteristics such as temperature, air quality and noise. In contrast this study measures students’ subjective perceptions of their physical school environment and explores how these perceptions along with socioeconomic status, gender and school attendance predict academic achievement. In addition, we also examined a range of other important variables that could be potential mediating factors between environmental perceptions and academic achievement. The study was conducted with 441, S5 students in five secondary schools in Scotland. Students completed a questionnaire that measured their perceptions of their school environment, their behaviour in school, and their learning goals. In addition data on student academic achievement, attendance and socioeconomic status was provided by the local Authority. Regression analysis indicates that students’ subjective perceptions of their physical school environment, along with attendance, socioeconomic status and gender are all significant predictors of academic achievement. In addition, subsequent analysis indicates that the impact of students’ subjective perceptions of their physical school environment on academic achievement is mediated by important ‘in-school behaviours’, namely engaging behaviour and environmental difficulty. The implications of these findings are discussed in terms of the direct and indirect impact of student perceptions of their school environment on their academic achievement.